Nitrogen in the marine environment - Capone, Douglas G. (Elsevier, 2008)
Since the first edition of Nitrogen in the Marine Environment was published in 1983, it has been recognized as the standard in the field. In the time since the book first appeared, there has been tremendous growth in the field with unprecedented discoveries over the past decade that have fundamentally changed the view of the marine nitrogen cycle. As a result, this Second Edition contains twice the amount of information that the first edition contained. This updated edition is now available online, offering searchability and instant, multi-user access to this important information.
Keywords: Nitrogen cycle.; Marine biology.; elektronické knihy; electronic books